1989
DOI: 10.1111/j.1365-3083.1989.tb01135.x
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Human B‐Cell Proliferation by a Monoclonal Antibody to CD43

Abstract: Monoclonal antibodies (MoAb) to human leucocyte sialoglycoprotein, CD43, have been shown to deliver mitogenic signals to human T cells or to enhance T-cell proliferation induced by concanavalin A, anti-CD3 antibodies or phorbol ester. In this paper, we studied the effects of anti-CD43 MoAb B1B6 on the activation of human B cells. Anti-CD43 MoAb B1B6 was not mitogenic by itself for human B cells. However, when added together with TPA, both resting and in vivo activated tonsillar B cells, containing 5-10% and ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1990
1990
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Cell suspension studies have identified CD43 on virtually all T cells, on -25-30% ofperipheral and umbilical cord blood B cells and on 10-15% of tonsillar B cells ( 3 , 2 3 ) . CD43 expression has been associated with activation and differentiation of B cells as well as being found more frequently on B cells synthesizing IgG rather than IgM (22)(23)(24)(25). CD43 has also been associated with T-cell and monocyte activation (10,12).…”
Section: Discuss I0 Nmentioning
confidence: 99%
See 1 more Smart Citation
“…Cell suspension studies have identified CD43 on virtually all T cells, on -25-30% ofperipheral and umbilical cord blood B cells and on 10-15% of tonsillar B cells ( 3 , 2 3 ) . CD43 expression has been associated with activation and differentiation of B cells as well as being found more frequently on B cells synthesizing IgG rather than IgM (22)(23)(24)(25). CD43 has also been associated with T-cell and monocyte activation (10,12).…”
Section: Discuss I0 Nmentioning
confidence: 99%
“…(1,3,4,13). Functionally, it is associated with lymphocyte activation and differentiation and possibly maintenance of cellular "integrity" (3,12,(21)(22)(23)(24)(25).…”
mentioning
confidence: 99%
“…6 -10). Like CD164, the PSGL-1, CD34, and CD43 sialomucins may also function as signaling molecules that regulate cell proliferation (11)(12)(13)(14)(15)(16)(17)(18), possibly by enabling other receptor-ligand interactions to occur. These diverse functions are thought to be the result, at least in part, of cell type-and stage-specific oligosaccharide modifications, particularly those involving sialylation (19 -22; reviewed in Refs.…”
Section: Cd38mentioning
confidence: 99%
“…[29][30][31][32] In addition, antibodies to CD43 have been shown to activate monocytes, B lymphocytes, and dendritic, mast, and natural killer cells. [33][34][35][36][37][38][39] CD43 binds major histocompatibility complex (MHC) class I molecules and activates T lymphocytes in a manner independent of both the T lymphocyte receptor/CD3 complex and CD28. [40][41][42][43] The activation signals of this pathway are mediated through phosphorylation of the intracellular domain of CD43 and its physical interaction with the tyrosine kinases Fyn and Lck and the serine/threonine kinase STANK.…”
Section: Introductionmentioning
confidence: 99%